Metformin: (future) best friend of the radiation oncologist?. (October 2020) - Chevalier, Benjamin; Pasquier, David; Lartigau, Eric Felix; Chargari, Cyrus; Schernberg, Antoine; Jannin, Arnaud; Mirabel, Xavier; Vantyghem, Marie-Christine; Escande, Alexandre
Highlights: Metformin is an antidiabetic drug with potentially radiosensitizing properties. Preclinical data propose numerous mechanisms. Retrospective studies suggest benefits in PFS and OS in multiples localizations. Metformin could also limit RT-induced toxicities on healthy tissue. Several clinical trials are ongoing. Abstract: Several molecules are being investigated for their ability to enhance the anti-tumor effect of radiotherapy. The widely prescribed antidiabetic drug metformin has been suggested to possess anti-cancer activity; data indicate that metformin could also enhance radiation sensitivity. The purpose of this review is to summarize current knowledge on the specific effect of metformin in the field of RT, while also discussing the many unknowns that persist. Preclinical models point to multiple mechanisms involved in the radiosensitizing effects of metformin that are mainly linked to mitochondrial complex I inhibition and AMP-activated protein kinase. Transposition of results from bench to bedside will be discussed through the lens of the drug concentration, its potential limits in human settings, and possible alternatives. Clinical data suggest metformin improves progression-free and overall survival in patients for many different cancers treated with RT; nevertheless, the results are not always consistent. The main limitations of the reviewed literature are the retrospective nature of studies, and most of the time, a lack of information on MTF treatment duration and the administered dosages. Despite these limitations, the possible mechanisms of the role of metformin and its utility in enhancing radiotherapy treatments are analyzed. Ongoing clinical trials are also discussed.